2012
DOI: 10.7314/apjcp.2012.13.6.2935
|View full text |Cite
|
Sign up to set email alerts
|

Biological Response Modifiers Influence Structure Function Relationship of Hematopoietic Stem and Stromal Cells in a Mouse Model of Leukemia

Abstract: Biological response modifiers (BRMs) can alter interactions between the immune system and cancer cells to boost, direct, or restore the body's ability to fight disease. Mice with ethylnitrosourea-(ENU) induced leukemia were here used to monitor the therapeutic efficacy of lipopolysaccaride (LPS), Bacillus Calmette Guerin (BCG) and sheep erythrocytes (SRBC). Flow cytometry based CD34+ positivity analysis, clonogenicity, proliferation and ultrastructure studies using scanning electron microscopy (SEM) of stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In another paper from the same group, the immunotherapeutic effect of BCG was attributed to gd Tcells' anti-tumor response induced by cytokines from type-1 dendritic cells (64). In a leukemia mouse model, Basu et al have shown that BCG could increase survival thanks to its stimulating effect on hematopoietic regeneration (65). In a VX-2 squamous cell carcinoma rabbit model in which rabbits are injected with tumor cells on two sites (auricle and lung), Hamamoto et al looked at the effect of intralesional BCG on radio-frequency ablation of the lung tumor.…”
Section: Bcg As Direct Anticancer Therapy (Alone or In Combination With Existing Treatments)mentioning
confidence: 99%
See 1 more Smart Citation
“…In another paper from the same group, the immunotherapeutic effect of BCG was attributed to gd Tcells' anti-tumor response induced by cytokines from type-1 dendritic cells (64). In a leukemia mouse model, Basu et al have shown that BCG could increase survival thanks to its stimulating effect on hematopoietic regeneration (65). In a VX-2 squamous cell carcinoma rabbit model in which rabbits are injected with tumor cells on two sites (auricle and lung), Hamamoto et al looked at the effect of intralesional BCG on radio-frequency ablation of the lung tumor.…”
Section: Bcg As Direct Anticancer Therapy (Alone or In Combination With Existing Treatments)mentioning
confidence: 99%
“…In a leukemia mouse model, Basu et al. have shown that BCG could increase survival thanks to its stimulating effect on hematopoietic regeneration ( 65 ). In a VX-2 squamous cell carcinoma rabbit model in which rabbits are injected with tumor cells on two sites (auricle and lung), Hamamoto et al.…”
Section: Bcg Vaccinementioning
confidence: 99%